More on the harvesting aid contract - Puślecki, Damian (Przegląd Prawa Rolnego, 2019)
The aim of the article is to answer the question to what extent a contract for harvesting aid constitutes the grounds for a legal relationship characterised by the equality of parties and whether it is an obligation of diligence or result. The conclusion is that a contract for harvesting aid is a contract which is binding upon the parties bilaterally, as well as being causative, consensual and payable. It is an agreement regulating civil law relationships between a farmer conducting agricultural activity and a helper assisting the farmer in an agricultural holding during harvest. The scope of the helper’s activities defined by the farmer in the contract may determine whether the helper’s performance makes the obligation of a result or a diligence character. This, in turn, will depends on the accuracy of the specification of the help and the method of payment of remuneration agreed by the parties.